CHOICE OF “TIME WINDOW” IN CARRYING OUT IPO OF RUSSIAN COMPANIES - L. V. Tokun; A. G. Berg (Вестник университета)
The article is devoted to the problems of public placement of companies on the Russian stock market. The arguments proving necessity of raising capital through public offering in the Russian Federation have been presented. Foreign and domestic researches of the influence of the time factor during public offering have been considered. The necessity of taking into account the time factor when making a decision on the company’s IPO has been identified and justified. The Russian stock market and its main trends have been analysed, the possibility of applying foreign experience on the Russian market has been assessed. Based on the conducted research, it has been proposed to promote the creation of favorable «Windows», which will help eliminate weaknesses, as well as provide evidence-based regulation in order to create favorable conditions for IPO.